The Influence of Independent Entrepreneurs and Independent Campus on Startup Developments by Realizing Creative Ideas as Moderating Variables - Wulan, Rizki Ayu Wulandari; Yani, Ari Soeti (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to determine the effect of independent entrepreneurs’ influence and independent campuses on startup development by realizing creative ideas as a moderating variable. Research methodology: Startup, independent entrepreneur, independent campus, startup development, and creative ideas as moderating variables, Quantitative, SmartPLS, and Questioner. Results: Independent entrepreneurs have a significant positive effect on startup development. An independent campus has a positive and significant effect on startup development. Creative ideas have a positive and significant effect on start-up development. The moderation of creative ideas has a significant effect and can moderate the effect of the Independent Entrepreneur program on startup development. The moderation of creative ideas has a significant influence and can moderate the effect of independent campuses on startup development. Limitations: This study was conducted with a limited sample, both in terms of sample size and population diversity; therefore, new variables are needed to further strengthen the results. Contribution: This research is expected to provide more insight for the younger generation to be eager to establish startups and compete in the future.